INVESTIGATING SPEAKING ANXIETY OF THE TENTH GRADE STUDENTS AT SMA NEGERI 4 SINGARAJA - N A K Dewi; A A I N Marhaeni; G A P Suprianti (Universitas Pendidikan Ganesha, 2018)
This present study was aimed at investigating the levels of students’ speaking anxiety and the most dominant factor influencing students’ speaking anxiety. This study was a cross sectional survey with quantitative method. The population of this study was the tenth grade students of SMA Negeri 4 Singaraja in academic year 2017/2018. Simple random sampling was used as the sampling technique. The total number of the sample was 110 students who were chosen randomly from 11 classes. The data was gathered by using questionnaire. Then, it was analyzed by finding out the percentage of the students’ speaking anxiety level and mean score for the most dominant factor influencing students’ speaking anxiety. The result of this study showed that most of the students were in mildly anxious level with the percentage 51%. It followed by 24% students felt anxious and 24% of them felt relaxed. Additionaly, 1% student was categorised as very anxious level and only 1% of was in very relaxed level. Finally, in this present study, it was found that cognitive factor was the most dominant factor influencing students speaking anxiety.